RELATED IMPACT FROM PRODUCT QUALITY AND BRAND IMAGE TOWARDS BUYING DECISIONS AS WELL AS ITS IMPLICATIONS TO CUSTOMER SATISFACTION AT FUJI YUSOKI KOGYO - Irawan, Ryan; Sitio, Arifin (Dinasti International Journal of Digital Business Management, 2021)
This research aims to find out those influence from Product Quality, and Brand Image towards Buying Decisions and its Implications to Customer Satisfaction at Fuji Yusoki Kogyo. This type of research was catagorized as descriptive analytics research. While population was customers from Fuji Yusoki Kogyo totalling of 56 customers according to December 2020 company's internal data. The analysis technique used path analysis through SmartPLS version 3.3. The results from this research was indicate that (1) Product Quality has huge impact to Buying Decision (2) Brand Image has significant influence over Buying Decision (3) Buying Decision has undefinable effect to Customer Satisfaction (4) Product Quality has marked affects towards Customer Satisfaction, and (5) Brand Image has huge impact on Customer Satisfaction